2023
DOI: 10.1002/2211-5463.13544
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LRP/LR with siRNA inhibits several cancer hallmarks in lung cancer cells

Abstract: The incidence and mortality rates of cancer are growing rapidly worldwide, with lung cancer being the most commonly occurring cancer in males. Human carcinomas circumvent the inhibitory pathways induced by DNA damage and senescence through the upregulation of telomerase activity. The 37 kDa/67 kDa laminin receptor (LRP/LR) is a cell surface receptor which plays a role in several cancer hallmarks, including metastasis, angiogenesis, cell viability maintenance, apoptotic evasion, and mediating telomerase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…It has been shown that once LRP/LR has bound to laminin, LRP/LR can then interact with focal adhesion kinase and this interaction then activates the PI3‐kinase/AKT and MEK/ERK1/2 pathways, which are directly related to proliferation and longevity [ 31 ]. It has further been established that LRP/LR plays a key role in mediating telomerase activity [ 4 , 6 , 7 , 8 ], whereby LRP/LR increases telomerase activity to promote cell viability and prevent cellular senescence, as shown by the reduction in gamma H2AX (which marks sites of DNA damage and DNA breaks) and the senescence biomarker β‐galactosidase [ 6 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that once LRP/LR has bound to laminin, LRP/LR can then interact with focal adhesion kinase and this interaction then activates the PI3‐kinase/AKT and MEK/ERK1/2 pathways, which are directly related to proliferation and longevity [ 31 ]. It has further been established that LRP/LR plays a key role in mediating telomerase activity [ 4 , 6 , 7 , 8 ], whereby LRP/LR increases telomerase activity to promote cell viability and prevent cellular senescence, as shown by the reduction in gamma H2AX (which marks sites of DNA damage and DNA breaks) and the senescence biomarker β‐galactosidase [ 6 , 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a 96-well plate, the TRAP reaction mixture and 2 lL of the standardised protein samples solution, for a total of 1 lg, were loaded into each well to a final volume of 12.5 lL. This reaction Mastermix consisted of LunaÒ Universal qPCR Mastermix (New England Biolabs, Ipswich, MA, USA), TS and ACX primers (as described by Bignoux et al [8]), EGTA and PCR-grade water. The CFX96 TM Touch qPCR System (Bio-Rad) was employed to perform qPCR analysis on all samples, using the following cycling parameters: One cycle of 30 min at 37 °C (telomere extension step), and 2 min at 95 °C, followed by 45 cycles of amplification with denaturation at 95 °C for 15 s, annealing at 59 °C for 60 s, and extension at 45 °C for 10 s. Minus telomerase (consisting only of CHAPS lysis buffer), no template (PCR-grade water) and heat-treated (incubated at 90 °C for 10 min to inactivate any telomerase activity) negative controls were included.…”
Section: Telomerase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis revealed that melanoma cells displayed high levels of RPSA on their cell surface and the treatment with IgG1–iS18 antibody determined a significant reduction of the adhesive potential to LM and the invasive capacity of malignant melanoma cells, confirming previous results reported in several types of cancer cells [ 75 78 ]. For instance, in A549 lung cancer cell line, downregulation of RPSA with specific siRNA, inhibited cellular migration activity, as evaluated by scratch motility assay [ 79 ]. From a mechanistic point of view, proteomic analysis performed in pancreatic cancer cells, revealed that RPSA interacted with Integrin alpha 6 (ITGA6) and that they colocalized on the plasma membrane as showed by immunofluorescence analysis.…”
Section: Prp C and Rpsa Involvement In Proliferati...mentioning
confidence: 99%
“…The authors postulated that RPSA upregulation may enhance telomerase activity [ 122 , 123 ]. Reversely, siRNA-mediated RPSA knock-down impeded telomerase activity in breast and lung cancer cells [ 79 , 121 ]. Likewise, a significant decrease in telomerase activity and hTERT expression levels was observed in late-stage CRC cells via RPSA siRNA technology, resulting in genetic instability and activation of DDR pathway [ 54 , 124 ].…”
Section: Genome Instability and Mutation: The Role Of Prp C...mentioning
confidence: 99%